2011
DOI: 10.1007/s13595-011-0129-4
|View full text |Cite
|
Sign up to set email alerts
|

ITS-based comparison of endophytic mycota in twigs of native Populus nigra and cultivated P. x euramericana (cv. I-214) stands in Northern Spain

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Analysis by NMDS and MRPP showed that endophyte assemblages differed according to host species, which is consistent with findings of other studies that compared hosts of different genera (Petrini and Fisher, 1990), the same genus (Collado et al, 2000) and even a hybrid compared with its parent (Martín-García et al, 2012).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Analysis by NMDS and MRPP showed that endophyte assemblages differed according to host species, which is consistent with findings of other studies that compared hosts of different genera (Petrini and Fisher, 1990), the same genus (Collado et al, 2000) and even a hybrid compared with its parent (Martín-García et al, 2012).…”
Section: Discussionsupporting
confidence: 90%
“…The most abundant species observed in the present study (A. pullulans, Penicillium spp., A. niger, Cladosporium spp. and A. alternata complex) are ubiq- (Fisher et al, 1994;Collado et al, 1999;Nicolotti et al, 2003), Pinus (Martín-Pinto et al, 2004;Zamora et al, 2008;Botella et al, 2010), Populus (Santamaría and Diez, 2005;Martín-García et al, 2011;Martín-García et al, 2012), Eucalyptus (Bettucci and Alonso, 1997), Betula (Green, 2004), Picea (Johnson and Whitney, 1992) and Calocedrus (Petrini and Carroll, 1981). Conversely, other species isolated are known secondary and opportunistic pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the fungal community was clearly dominated by the yeast-like fungus A. pullulans. This species is a very abundant colonizer of plant surfaces but was also often isolated as an endophyte from trees (Albrectsen et al, 2010;Martin-Garcia et al, 2012), including common ash (Slavikova et al, 2007;Davydenko et al, 2013;Hanackova et al, 2017a). As a pleiomorphic fungus, it is known to switch between yeast and mycelial forms in response to its environmental conditions (Ramos and García Acha, 1975;Campbell et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…tenuissima, A. pullulans, B. bassiana, B. mediterranea, F. oxysporum, H. lixii, H. dematioides, N. oryzae, P. glabrum, S. strictum, S. fimicola, T. harzianum, T. viride, and Xylaria sp. (Chapela 1989;Fisher & Petrini 1992;Bettucci & Alonso 1997;Collado et al 1999;Santamar ıa & Diez 2005;Gonthier et al 2006;Jaklitsch et al 2006;Unterseher & Schnittler 2010;Mart ın-Garc ıa et al 2011). Therefore, half of the taxa inhabiting Scots pine twigs were host-generalists, and the other half were coniferous or pine specialists.…”
Section: Discussionmentioning
confidence: 99%